Combined EUS-Guided Abdominal Cavity Drainage and Cystogastrostomy for the Ruptured Pancreatic Pseudocyst - Ge Nan; Sun Siyu; Liu Xiang; Wang Sheng; Wang Guoxin (Gastroenterology Research and Practice)
Background. Endoscopic-Ultrasonography- (EUS-) guided puncture and drainage of pancreatic pseudocyst is currently one of the most widely accepted nonsurgical treatments. To date, this technique has only been used for pancreatic pseudocysts adhesive to the gastric wall. This study introduces the technique of EUS-guided pseudocyst drainage and additional EUS-guided peritoneal drainage for the ruptured pseudocyst. Methods. Transmural puncture and drainage of the cyst were performed with a 19 G needle, cystotome, and 10 Fr endoprosthesis. Intraperitoneal drainage was performed with a nasobiliary catheter when rupture of pseudocyst occurred. The entire procedure was guided by the echoendoscope. Results. A total of 21 patients, 8 men and 13 women, with a mean age of 36 years, were included in this prospective study. All of the pseudocysts were successfully drained by EUS. Peritoneal drainage was uneventfully performed in 4 patients. There were no severe complications. Complete pseudocyst resolution was established in all patients. Conclusion. The technique of EUS-guided transmural puncture and drainage, when combined with abdominal cavity drainage by a nasobiliary catheter, allows successful endoscopic management of pancreatic pseudocysts without adherence to gastric wall.